A method for preparing silicon-coated hexagonal boron nitride

By modifying the surface hydroxylation of hexagonal boron nitride and forming a silicon oxygen layer, combining the melt cooling method of silicon powder and mineralizer, the effective coating of hexagonal boron nitride by silicon is achieved, solving the problem of poor dispersion performance in organic matter, and improving the dispersion performance and thermal conductivity.

CN116216660BActive Publication Date: 2025-03-25FOSHAN SANSHUI JINGE NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211696387.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-03-25
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The lack of active groups on the surface of hexagonal boron nitride makes it difficult to disperse in organic matter, limiting its application range.

Method used

By surface hydroxylation modification of hexagonal boron nitride, a silicon oxygen layer is formed, and mixed with silicon powder and mineralizer, the coating of hexagonal boron nitride by silicon powder is achieved by melt cooling.

Benefits of technology

The dispersion performance of boron nitride was successfully improved, the problem of uneven powder size during sintering was improved, and the thermal conductivity of the modified boron nitride-filled composite material was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116216660B_ABST
    Figure CN116216660B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing silicon-coated hexagonal boron nitride, wherein the method uses hexagonal boron nitride as a raw material, performs hydroxylation and coupling agent modification treatment on its surface, and forms hexagonal boron nitride containing a silicon oxide layer; and then melts and calcines with raw materials such as silicon powder and a mineralizer under protective atmosphere conditions to obtain silicon-coated hexagonal boron nitride. The present invention successfully achieves effective coating of hexagonal boron nitride with silicon powder, and the obtained silicon-coated hexagonal boron nitride powder has uniform size and excellent dispersion performance, greatly improves the compatibility of boron nitride in a polymer matrix, and the raw materials are simple and easy to obtain, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic non-metallic materials, and in particular relates to a preparation method of silicon-coated hexagonal boron nitride. Background Art

[0002] The crystal plane of hexagonal boron nitride (h-BN) has a similar structure to graphite, so it has many unique properties of graphitized planes, such as superb thermal conductivity, good corrosion resistance, lubricity and oxidation resistance. It has broad application prospects in insulating materials, refractory materials, heat dissipation materials, high-temperature solid lubricants, superhard materials, integrated circuit packaging, antioxidant additives, etc. However, due to the very stable chemical properties of hexagonal boron nitride and the lack of active groups on the surface, it is difficult to disperse in organic matter, which greatly limits the scope of application of boron nitride.

[0003] In recent years, many studies have been devoted to the preparation of modified boron nitride materials with good dispersion properties. Invention patent CN87100500 discloses a method for preparing a boron-rich polycrystalline cubic boron nitride abrasive, using boron-rich polycrystalline cubic boron nitride, without adding sintering aids, and sintering at high temperature and high pressure to obtain a well-sintered polycrystalline. However, this method uses boron-rich polycrystalline cubic boron nitride as a raw material, which is not easy to obtain and expensive, and the required high temperature and high pressure conditions are harsh, so it is difficult to promote and apply. Patent No. CN112588259A discloses a method for preparing a graphene and boron nitride composite material, using graphene oxide, boron nitride and a mineralizer, and obtaining a good sintered body after high temperature sintering. However, the size of the obtained boron nitride sintered body is uneven, and there is a phenomenon of abnormal grain growth, which limits its application prospects. Summary of the invention

[0004] Based on the problems described in the background technology, the purpose of the present invention is to provide a method for preparing silicon-coated hexagonal boron nitride. The preparation method provided by the present invention can achieve effective coating of hexagonal boron nitride with silicon, improve the dispersion performance of boron nitride, and improve the problem of uneven powder size during sintering.

[0005] The present invention provides a silicon-coated hexagonal boron nitride, and its specific formation process and principle are as follows: first, the surface of hexagonal boron nitride is modified by hydroxylation, so that the silane coupling agent is convenient to bond silicon oxygen on the surface of hexagonal boron nitride, and then the hexagonal boron nitride modified with a silicon oxygen layer, silicon powder and a mineralizer are mixed, and the silicon powder is melt-coated on the hexagonal boron nitride powder by a melting cooling method. Due to the presence of oxygen atoms, silicon oxygen is negatively charged; and after melting, the silicon powder has a certain loss due to the thermal activation of electrons, and the whole is positively charged. The two are electrostatically adsorbed, and then in the process of melting coating, the silicon oxygen layer is used as a connecting medium, so that the silicon powder is bonded to the surface of the hexagonal boron nitride through silicon oxygen. At the same time, the mineralizer reduces the melting point of the hexagonal boron nitride, so that the surface of the hexagonal boron nitride is liquefied, so as to achieve the full coverage of the hexagonal boron nitride by the silicon powder. The results of the embodiment show that the present invention successfully achieves the coating of silicon on the hexagonal boron nitride powder.

[0006] The present invention provides a method for preparing silicon-coated hexagonal boron nitride powder, comprising the following steps:

[0007] (1) preparing silicon oxide layer coated hexagonal boron nitride powder;

[0008] (2) The silicon oxide layer-coated hexagonal boron nitride powder is mixed with silicon powder and a mineralizer, and first calcined under argon at a calcination temperature of 1450°C for 1 hour, and then calcined under nitrogen or ammonia at a calcination temperature of 1500-1900°C for 1-8 hours. After the sintered body is naturally cooled to room temperature, it is ball milled for 5-60 minutes to obtain silicon-coated hexagonal boron nitride.

[0009] The silicon oxide layer-coated hexagonal boron nitride powder prepared in step (1) specifically comprises the following steps:

[0010] (1) Preparation of hydroxylated boron nitride: 10-100 μm hexagonal boron nitride powder and a certain mass concentration of acid solution or alkaline solution are stirred at room temperature at a speed of 50-300 r / min for 6-24 hours to obtain a suspension, the suspension is washed three times with distilled water and then filtered to obtain a filter cake, and the filter cake is placed in a constant temperature drying oven at 80° C. and dried for 12-24 hours to obtain hydroxylated boron nitride powder;

[0011] (2) The hydroxylated boron nitride is mixed with a certain amount of distilled water to form a suspension, and then a certain amount of organic solvent is added to form a mixed solution, and a silane coupling agent is added to the mixed solution in a certain proportion, and the mixture is stirred at 50 to 120° C. and a rotation speed of 50 to 300 r / min for 6 to 24 hours. After the reaction is completed, the mixture is cooled to room temperature, washed three times with anhydrous ethanol, and then filtered to obtain a filter cake, and the filter cake is placed in a constant temperature drying oven at 80° C. and dried for 12 to 24 hours to obtain a silicon oxide layer-coated hexagonal boron nitride powder.

[0012] In the step (2), the mass ratio of the silicon oxide layer coated hexagonal boron nitride powder to silicon powder and the mineralizer is 100-200:10-50:0.5-10; the mineralizer is one or more of scandium-containing oxides, yttrium-containing oxides, and lanthanum-containing oxides.

[0013] The silicon powder is metallic silicon powder, and has the shape of spherical particles and a median diameter D50 of 1 to 5 μm.

[0014] The mass ratio of the hexagonal boron nitride to the acid solution or the alkaline solution is 1-100:20-2000; the acid solution or the alkaline solution is one of hydrogen peroxide, sodium hydroxide, potassium hydroxide, concentrated sulfuric acid and concentrated nitric acid.

[0015] The mass ratio of the hydroxylated boron nitride to distilled water, organic solvent and silane coupling agent is 1:50-100:10-50:0.01-0.05; the organic solvent includes one or more of cyclohexane, anhydrous ethanol and acetone; the silane coupling agent includes one or more of trimethylsiloxane, dimethyldiethoxysilane, diethylsiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and hexamethyldisiloxane.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] (1) The present invention successfully achieves effective silicon coating of hexagonal boron nitride, thereby greatly improving the dispersion performance of boron nitride, which can be effectively dispersed in organic solvents, further improving the thermal conductivity of the modified boron nitride filled composite material.

[0018] (2) Compared with boron nitride sintered under the same sintering conditions, the silicon-coated hexagonal boron nitride powder prepared by sintering in the present invention has a concentrated particle size distribution, which improves the problem of uneven powder size during the sintering process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of the metallic silicon powder raw material in Example 1.

[0020] Figure 2 This is the SEM image of the hexagonal boron nitride powder coated with silicon oxide layer prepared in Example 1.

[0021] Figure 3 The SEM image (left) and XRD image (right) of the hexagonal boron nitride powder raw material in Example 1.

[0022] Figure 4 The SEM image and XRD pattern of the silicon-coated hexagonal boron nitride prepared in Example 1 (right).

[0023] Figure 5 This is the energy spectrum of the hexagonal boron nitride powder raw material in Example 1.

[0024] Figure 6 This is the energy spectrum of the silicon-coated hexagonal boron nitride prepared in Example 1.

[0025] Figure 7 This is the SEM image of the product prepared in Comparative Example 1.

[0026] Figure 8 This is the SEM image of the product prepared in Comparative Example 2.

[0027] Fig. 9 This is the SEM image of the product prepared in Comparative Example 3. DETAILED DESCRIPTION

[0028] The embodiments described below specifically illustrate the above contents of the present invention, and particularly illustrate that, based on the principles of the present invention, several adjustments and improvements may be made, and these adjustments and improvements are also considered to be within the protection scope of the embodiments of the present invention.

[0029] Example 1

[0030] (1) Preparation of silicon oxide layer coated hexagonal boron nitride powder:

[0031] 10g of 10μm hexagonal boron nitride powder and 200g of 10% potassium hydroxide solution are stirred at room temperature at a speed of 50r / min for 6h to obtain a suspension, the suspension is washed three times with 50mL of distilled water and then filtered to obtain a filter cake, the filter cake is placed in a constant temperature drying oven at 80°C and dried for 12h to obtain hydroxylated boron nitride powder; the above 10g of hydroxylated boron nitride and 500g of distilled water are mixed to form a suspension, 100g of anhydrous ethanol is added to form a mixed solution, 0.1g of triethoxysilane is added to the mixed solution, and the mixture is stirred at 50°C and a speed of 50r / min for 6h. After the reaction is completed, it is cooled to room temperature, washed three times with 50mL of anhydrous ethanol and then filtered to obtain a filter cake, the filter cake is placed in a constant temperature drying oven at 80°C and dried for 12h to obtain silicon oxide layer coated hexagonal boron nitride powder.

[0032] (2) Preparation of silicon-coated hexagonal boron nitride powder:

[0033] The above-mentioned silicon oxide layer-coated hexagonal boron nitride powder is mixed with 1μm metal silicon powder and scandium oxide in a mass ratio of 200:20:1. After mixing evenly, the mixture is poured into a crucible and first calcined under argon at a calcination temperature of 1450°C for 1 hour. Then, the mixture is calcined under nitrogen at a calcination temperature of 1500°C for 1 hour. After the sintered body is naturally cooled to room temperature, it is ball-milled for 5 minutes to obtain silicon-coated hexagonal boron nitride.

[0034] Example 2

[0035] (1) Preparation of silicon oxide layer coated hexagonal boron nitride powder:

[0036] 20g30μm hexagonal boron nitride powder and 500g20% sodium hydroxide solution were stirred at room temperature at a speed of 80r / min for 12h to obtain a suspension, the suspension was washed three times with 80mL of distilled water and then filtered to obtain a filter cake, the filter cake was placed in a constant temperature drying oven at 80℃ and dried for 12h to obtain hydroxylated boron nitride powder; the above 20g hydroxylated boron nitride and 1500g of distilled water were mixed to form a suspension, 300g of anhydrous ethanol was added to form a mixed solution, 0.4g of trimethoxysilane was added to the mixed solution, and stirred at 80℃ and a speed of 80r / min for 12h, after the reaction was completed, it was cooled to room temperature, washed three times with 80mL of anhydrous ethanol and then filtered to obtain a filter cake, the filter cake was placed in a constant temperature drying oven at 80℃ and dried for 12h to obtain silicon oxide layer coated hexagonal boron nitride powder.

[0037] (2) Preparation of silicon-coated hexagonal boron nitride powder:

[0038] The above silicon oxide layer coated hexagonal boron nitride powder is mixed with 2μm metal silicon powder and yttrium oxide in a mass ratio of 100:15:1. After mixing evenly, pour it into a crucible and calcine it under argon at a calcination temperature of 1450°C for 1 hour. Then, calcine it under nitrogen at a calcination temperature of 1700°C for 2 hours. After the sintered body is naturally cooled to room temperature, it is ball milled for 10 minutes to obtain silicon-coated hexagonal boron nitride.

[0039] Example 3

[0040] (1) Preparation of silicon oxide layer coated hexagonal boron nitride powder:

[0041] 30g of 60μm hexagonal boron nitride powder and 600g of 30% concentration hydrogen peroxide solution are stirred at room temperature at a speed of 100r / min for 24h to obtain a suspension, the suspension is washed three times with 100mL of distilled water and then filtered to obtain a filter cake, the filter cake is placed in a constant temperature drying oven at 80℃ and dried for 24h to obtain hydroxylated boron nitride powder; the above 30g of hydroxylated boron nitride and 3000g of distilled water are mixed to form a suspension, 900g of anhydrous ethanol is added to form a mixed solution, 0.9g of dimethyldiethoxysilane is added to the mixed solution, and the mixture is stirred at 120℃ and a speed of 100r / min for 24h. After the reaction is completed, it is cooled to room temperature, washed three times with 100mL of anhydrous ethanol and then filtered to obtain a filter cake, the filter cake is placed in a constant temperature drying oven at 80℃ and dried for 24h to obtain silicon oxide layer coated hexagonal boron nitride powder.

[0042] (2) Preparation of silicon-coated hexagonal boron nitride powder:

[0043] The above silicon oxide layer coated hexagonal boron nitride powder is mixed with 3μm metal silicon powder and lanthanum oxide in a mass ratio of 100:20:2. After mixing evenly, the mixture is poured into a crucible and first calcined under argon at a calcination temperature of 1450°C for 1 hour, and then calcined under nitrogen at a calcination temperature of 1800°C for 2 hours. After the sintered body is naturally cooled to room temperature, it is ball milled for 15 minutes to obtain silicon-coated hexagonal boron nitride.

[0044] Comparative Example 1

[0045] 10 g of 10 μm hexagonal boron nitride powder raw material and 1 g of 1 μm metal silicon powder as in Example 1 were weighed and mixed in a ball mill for 5 min to obtain a mixed powder filler.

[0046] Comparative Example 2

[0047] Weigh 10g of the same hydroxylated hexagonal boron nitride powder as in Example 1 (without silicon-oxygen modification), mix it evenly with 1g of 1μm metallic silicon powder and 0.05g of scandium oxide, and pour it into a crucible. First, calcine it under argon at a calcination temperature of 1450°C and a holding time of 1h. Then, calcine it under nitrogen at a calcination temperature of 1500°C and a holding time of 1h. After the sintered body is naturally cooled to room temperature, ball mill it for 5min to obtain the product.

[0048] Comparative Example 3

[0049] Weigh 10 g of the same silicon-oxygen hydroxylated hexagonal boron nitride powder as in Example 1, and directly mix it with 1 g of 1 μm metallic silicon powder in a crucible (without adding a mineralizer). First, calcine it under argon at a calcination temperature of 1450°C for 1 h, and then calcine it under nitrogen at a calcination temperature of 1500°C for 1 h. After the sintered body is naturally cooled to room temperature, it is ball-milled for 5 min to obtain the product.

[0050] The filling volume test method and standard are as follows:

[0051] Maximum filling amount: continuously add modified hexagonal boron nitride thermal conductive powder into 20g of 350cp vinyl silicone oil (3% hydrogen-containing silicone oil, 0.3% inhibitor, 0.5% platinum catalyst), place it in a vacuum stirring degassing machine after preliminary dispersion, set the speed to 700r / min, stir for 3min, and then use a calender to shape it into a gasket with a thickness of 2mm. Put the gasket in a 120℃ oven and dry it for 15min. Take out the gasket and cool it naturally to room temperature. If there is no powder falling off the surface of the gasket, the maximum filling amount is reached.

[0052] Table 1: Maximum filling amount of modified hexagonal boron nitride prepared in each case

[0053] serial number Boron Nitride Type Maximum filling amount Example 1 Silicon-coated hexagonal boron nitride 150 copies Example 2 Silicon-coated hexagonal boron nitride 170 copies Example 3 Silicon-coated hexagonal boron nitride 200 copies Comparative Example 1 Boron nitride / silicon mixed powder 50 servings Comparative Example 2 Unsiliconized Boron Nitride / Silicon Mixed Powder 60 servings Comparative Example 3 Silicon oxide boron nitride / silicon mixed powder 70 servings

[0054] From the attached figure and the data in Table 1, we can see that:

[0055] (1) According to the scanning electron microscope and XRD analysis, the comparative example 1 ( Figure 7 ) has no coating layer formed on the surface of hexagonal boron nitride, indicating that it is difficult to coat the metal silicon powder on the surface of hexagonal boron nitride by simple ball milling; secondly, the comparative example 2 ( Figure 8 ) and comparative example 3 without adding mineralizer ( Fig. 9 ) also does not form a coating layer on the surface of the hexagonal boron nitride; and the product ( Figure 4 ) The characteristic peaks of silicon were clearly observed, and its morphology changed from the original hexagonal flake to a spherical shape, and there was no similar Figure 1 The fine powder of metallic silicon powder indicates that Example 1 successfully prepared hexagonal boron nitride powder with silicon coating.

[0056] (2) The maximum filling amount of the silicon-coated hexagonal boron nitride powder of the present invention in 350cP vinyl silicone oil is increased by 2 to 4 times compared with other unsuccessfully coated comparative examples 1 to 3, indicating that the silicon-coated hexagonal boron nitride greatly improves the dispersion performance of boron nitride, enabling it to be effectively dispersed in organic solvents, further improving the thermal conductivity of the modified boron nitride-filled composite material.

[0057] It can be seen from the above embodiments that the present invention successfully realizes silicon coating of hexagonal boron nitride, thereby solving the drawback of the prior art that silicon and hexagonal boron nitride are difficult to bond to each other, and the coating cost is low, which is convenient for process promotion.

[0058] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing silicon-coated hexagonal boron nitride powder, characterized in that: The following steps are involved: (1) Preparation of silicon oxide layer coated hexagonal boron nitride powder: ① Preparation of hydroxylated boron nitride: 10-100 μm hexagonal boron nitride powder and a certain mass concentration of acid solution or alkaline solution are stirred at room temperature at a speed of 50-300 r / min for 6-24 hours to obtain a suspension, the suspension is washed three times with distilled water and then filtered to obtain a filter cake, and the filter cake is placed in a constant temperature drying oven at 80°C and dried for 12-24 hours to obtain hydroxylated boron nitride powder; ② The hydroxylated boron nitride is mixed with a certain amount of distilled water to form a suspension, and then a certain amount of organic solvent is added to form a mixed solution, and a silane coupling agent is added to the mixed solution in a certain proportion, and the mixture is stirred at 50 to 120°C and a speed of 50 to 300 r / min for 6 to 24 hours. After the reaction is completed, it is cooled to room temperature, washed three times with anhydrous ethanol, and then filtered to obtain a filter cake, and the filter cake is placed in a constant temperature drying oven at 80°C and dried for 12 to 24 hours to obtain a silicon oxide layer-coated hexagonal boron nitride powder; (2) The silicon oxide layer-coated hexagonal boron nitride powder is mixed with silicon powder and a mineralizer, and first calcined under argon at a calcination temperature of 1450°C for 1 hour, and then calcined under nitrogen or ammonia at a calcination temperature of 1500-1900°C for 1-8 hours. After the sintered body is naturally cooled to room temperature, it is ball milled for 5-60 minutes to obtain silicon-coated hexagonal boron nitride.

2. The method for preparing a silicon-coated hexagonal boron nitride powder according to claim 1, characterized in that: In the step (2), the mass ratio of the silicon oxide layer coated hexagonal boron nitride powder to silicon powder and the mineralizer is 100-200:10-50:0.5-10; the mineralizer is one or more of scandium-containing oxides, yttrium-containing oxides, and lanthanum-containing oxides.

3. The method for preparing a silicon-coated hexagonal boron nitride powder according to claim 1, characterized in that: The silicon powder is metallic silicon powder, and has the shape of spherical particles and a median diameter D50 of 1 to 5 μm.

4. The method for preparing a silicon-coated hexagonal boron nitride powder according to claim 2, characterized in that: The mass ratio of hexagonal boron nitride to the acid solution or alkaline solution in (1) is 1-100:20-2000; the acid solution or alkaline solution is one of hydrogen peroxide, sodium hydroxide, potassium hydroxide, concentrated sulfuric acid and concentrated nitric acid.

5. The method for preparing a silicon-coated hexagonal boron nitride powder according to claim 2, characterized in that: The mass ratio of hydroxylated boron nitride to distilled water, organic solvent and silane coupling agent in (2) is 1:50-100:10-50:0.01-0.05; the organic solvent includes one or more of cyclohexane, anhydrous ethanol and acetone; the silane coupling agent includes one or more of trimethylsiloxane, dimethyldiethoxysilane, diethylsiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and hexamethyldisiloxane.

Citation Information

Patent Citations

  • Preparation method of graphene and boron nitride composite material

    CN112588259A

  • Re-sintered boron-rich polycrystalline cabic boron nitride and method for making same

    CN87100500A

  • Method for producing silica-coated boron nitride particles and silica-coated boron nitride particles

    CN113498422A